The Effect of the Implementation of Animated Learning Videos on Increasing Students' Motivation and Learning Outcomes in Citizenship Education During the Covid 19 Pandemic In Junior High Schools - Aqshal Gustiara Mahardika Wahyu; Asri Wibawa Sakti (Universitas Pendidikan Indonesia (UPI), 2023)
This study aims to determine the effect of using instructional media in the form of animated videos on increasing learning motivation in junior high school students. This study used a quantitative research method with a correlative approach aimed at 10 students of grade 8 Junior High School Cikupa, Tangerang Indonesia. The data collection method was carried out by distributing questionnaires, post-tests, and pre-tests, analyzing, and describing the results. The results showed that previously students had not been able to absorb civic education material well because of the monotonous learning method. With the presentation of material with animated videos about norms and justice, it is seen that there is an increase in learning motivation which of course has an impact on learning outcomes by 7.59%.